Effects of reduced water quality on coral reefs in and out of no‐take marine reserves. Issue 1 (23rd September 2015) - Wenger, Amelia S.; Williamson, David H.; da Silva, Eduardo T.; Ceccarelli, Daniela M.; Browne, Nicola K.; Petus, Caroline; Devlin, Michelle J.
Abstract: Near‐shore marine environments are increasingly subjected to reduced water quality, and their ability to withstand it is critical to their persistence. The potential role marine reserves may play in mitigating the effects of reduced water quality has received little attention. We investigated the spatial and temporal variability in live coral and macro‐algal cover and water quality during moderate and major flooding events of the Fitzroy River within the Keppel Bay region of the Great Barrier Reef Marine Park from 2007 to 2013. We used 7 years of remote sensing data on water quality and data from long‐term monitoring of coral reefs to quantify exposure of coral reefs to flood plumes. We used a distance linear model to partition the contribution of abiotic and biotic factors, including zoning, as drivers of the observed changes in coral and macro‐algae cover. Moderate flood plumes from 2007 to 2009 did not affect coral cover on reefs in the Keppel Islands, suggesting the reef has intrinsic resistance against short‐term exposure to reduced water quality. However, from 2009 to 2013, live coral cover declined by ∼50% following several weeks of exposure to turbid, low salinity water from major flood plume events in 2011 and subsequent moderate events in 2012 and 2013. Although the flooding events in 2012 and 2013 were smaller than the flooding events between 2007 to 2009, the ability of the reefs to withstand these moderate floods was lost, as evidenced by a ∼20% decline in coral cover between 2011 to 2013. Although zoning (no‐take reserve or fished) was identified a significant driver of coral cover, we recorded consistently lower coral cover on reserve reefs than on fished reefs throughout the study period and significantly lower cover in 2011. Our findings suggest that even reefs with an inherent resistance to reduced water quality are not able to withstand repeated disturbance events. The limitations of reserves in mitigating the effects of reduced water quality on near‐shore coral reefs underscores the importance of integrated management approaches that combine effective land‐based management with networks of no‐take reserves.